Implementasi Pendidikan Progresif John Dewey di Era Pendidikan Saat Ini - Avrielita Pamungkas, Azila; Talitha Yesiana Rahmawati, Sofie (Journal of Information System and Education Development, 2025)
This article discusses the relevance of implementing John Dewey's progressive education, particularly the concept of Intelligent Action, in the context of modern education. Progressive education emphasizes learning based on real-life experiences, active student participation, and the development of critical thinking skills and social responsibility. This study employs a qualitative literature review method by analyzing six relevant scholarly articles. The results show that Dewey's progressive education principles strongly support the development of a flexible curriculum, project-based learning, and adaptive approaches to the demands of a changing era. The concept of Intelligent Action helps shape students to be reflective, creative, and capable of making intelligent decisions in facing the complexities of the modern world. Therefore, the application of Dewey’s progressive education principles must be continuously developed to create an innovative and strong-character generation in the era of globalization